The Gastroenterologist's Guide to Management of the Post‐Liver Transplant Patient. (June 2018) - Chascsa, David M.; Vargas, Hugo E.
Abstract : N/A: The management of the post‐liver transplant patient is complex and involves a large interdisciplinary team. After referral to a transplant center, evaluation and listing, and eventual transplantation, the patient is cared for closely by the transplant center. Once deemed ready for discharge, the patient returns to the primary care provider for ongoing management of the various issues that increase in incidence post transplant such as osteoporosis, cardiovascular, and renal diseases, as well as metabolic syndrome. The role of the gastroenterologist is not well defined, but certainly, he or she may be called upon for the initial evaluation and ongoing management of gastrointestinal as well as hepatobiliary issues. This includes but is not limited to the investigation of abnormal liver tests, non‐specific gastrointestinal complaints such as nausea, vomiting, or diarrhea, biliary complications, and even recurrent hepatic disease. Having familiarity with post‐transplant immunosuppressive agents, drug interactions, and potential infectious and malignancy‐related complications of transplant is essential, as the primary gastroenterologist may be expected in some situations to field the initial work‐up, if patient access to the transplant center is limited. The aim of this review is to summarize the gastroenterologist's role in the management of the post‐liver transplant patient.